MPLS technology in quality of service of the WAN network at the National University of Huancavelica. - Ramos Paucar, William Danty (2022)
The interconnection data network, between the headquarters and its branches of the National University of Huancavelica, is carried out through the Internet network, which causes the low quality of communication between the branches. The objective of the research was to evaluate the influence of the network model with MPLS technology in improving the quality of service in the WAN network. An explanatory experimental pre-test and post-test study was carried out in a simulation laboratory using the GNS3 and D-ITG software. The population and the sample consisted of the ten WAN networks, and the sampling was non-probabilistic, in each network the quality of service tests were carried out, with the three types of traffic: data, VoIP and Streaming, being the indicators delay, jitter and packet loss for each type of service. The results obtained with IP technology (Delay: 78ms to 292ms and Jitter: 68ms to 13.3ms) and in MPLS (Delay: 13ms to 157.3ms and Jitter: 5.9ms to 12.2ms). It is concluded that the MPLS technology significantly influences the improvement of the quality of communication service between the branches of the university.